2023
DOI: 10.1037/vio0000439
|View full text |Cite
|
Sign up to set email alerts
|

A dyadic analysis of partner maltreatment using an attachment-based diathesis–stress model: A lab-based study.

Abstract: Objectives: Interpersonal and contextual factors are increasingly acknowledged to play an important role in understanding intimate partner maltreatment, abuse, and aggression. Nevertheless, several gaps in the literature exist. First, there is little dyadic and observational research into partner maltreatment. Second, there is little application of theoretical models with an interpersonal focus to guide research, policy, and practice. The present study adopted a diathesis–stress framework to understand the dya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…These findings are consistent with previous research (Hadian & Amini, 2019;Jardine, Vannier, & Voyer, 2022;Knox et al, 2023;Mostova, Stolarski, & Matthews, 2022;Navabinejad, Rostami, & Parsakia, 2023;Parker et al, 2021;Schulsinger, 2022;Sevari & Talaeezadeh, 2015;Sidhu, Bhalla, & Ali, 2019;Suri & Kochhar, 2021;Wollny, Jacobs, & Pabel, 2020;Zmaczyńska-Witek, Komborska, & Rogowska, 2019) that has shown that emotional intelligence is an important factor in predicting marital satisfaction and relationship quality. Emotional intelligence allows individuals to better understand and manage their own emotions, as well as the emotions of their partners, leading to more effective communication and conflict resolution.…”
Section: Correlations Between Ei and MC Husbands And Wives (N=100)supporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with previous research (Hadian & Amini, 2019;Jardine, Vannier, & Voyer, 2022;Knox et al, 2023;Mostova, Stolarski, & Matthews, 2022;Navabinejad, Rostami, & Parsakia, 2023;Parker et al, 2021;Schulsinger, 2022;Sevari & Talaeezadeh, 2015;Sidhu, Bhalla, & Ali, 2019;Suri & Kochhar, 2021;Wollny, Jacobs, & Pabel, 2020;Zmaczyńska-Witek, Komborska, & Rogowska, 2019) that has shown that emotional intelligence is an important factor in predicting marital satisfaction and relationship quality. Emotional intelligence allows individuals to better understand and manage their own emotions, as well as the emotions of their partners, leading to more effective communication and conflict resolution.…”
Section: Correlations Between Ei and MC Husbands And Wives (N=100)supporting
confidence: 92%
“…Emotional intelligence allows individuals to better understand and manage their own emotions, as well as the emotions of their partners, leading to more effective communication and conflict resolution (Gottman et al, 2019;Knox et al, 2023). Gottman and colleagues (2019) state that emotional intelligence was positively associated with marital satisfaction, and negatively associated with marital conflicts.…”
Section: Introductionmentioning
confidence: 99%
“…However, the more severe, blatant, and repeated the behavior is, the more those labels apply. Recent studies involving both self-report and observational assessments of dehumanization in romantic relationships have shown that both the frequency and severity of behavior are important aspects of determining the level of perpetration of interpersonal dehumanization (Knox et al, 2022; Pizzirani et al, 2019, 2021).…”
Section: Beyond Social Cognition: Dehumanizing Behavior In Close Rela...mentioning
confidence: 99%
“…Regarding the association between the predictors of dehumanization and its enactment, this research has discovered various contemporaneous and developmental predictors of dehumanization. One contemporaneous predictor is attachment insecurity, which is associated with greater maltreatment of relationship partners involving the denial of human qualities (Knox et al, 2022; Morera et al, 2022,). Indeed, Knox et al (2022) found that perpetration of maltreatment (which includes coercion, manipulation, and dehumanization) is associated with the attachment insecurity of both the perpetrator and their partner.…”
Section: Beyond Social Cognition: Dehumanizing Behavior In Close Rela...mentioning
confidence: 99%
See 1 more Smart Citation